2012
DOI: 10.5005/jp-journals-10024-1096
|View full text |Cite
|
Sign up to set email alerts
|

Reattachment of Fractured Anterior Teeth—Determining Fracture Strength using Different Techniques: An in vitro Study

Abstract: Aim:The aim of this in vitro study was to evaluate and compare the shear bond strength of teeth reattached with sixth generation dentin bonding agent: Xeno III and microhybrid resin composite: Esthet-X, using three different techniques: (1) Simple reattachment, (2) overcontour and (3) internal dentinal groove. Methodology:A total of 70 human maxillary central incisors were selected and divided into four groups as follows. Group I: Control group comprised of 10 samples. Group II: Simple reattachment, group III:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…24 Overcontour: This technique involves preparation of a groove along the fracture line extending coronally and apically after reattaching the fragment. Srilatha et al 25 have reported a fracture strength recovery of 91.4% compared to a sound tooth, highest among all the above-mentioned techniques. Likewise, Reis et al 12 have reported the highest fracture strength recovery of 97.2% compared to sound tooth with composite overcontouring.…”
Section: Techniques For Fragment Reattachmentmentioning
confidence: 96%
See 2 more Smart Citations
“…24 Overcontour: This technique involves preparation of a groove along the fracture line extending coronally and apically after reattaching the fragment. Srilatha et al 25 have reported a fracture strength recovery of 91.4% compared to a sound tooth, highest among all the above-mentioned techniques. Likewise, Reis et al 12 have reported the highest fracture strength recovery of 97.2% compared to sound tooth with composite overcontouring.…”
Section: Techniques For Fragment Reattachmentmentioning
confidence: 96%
“…23 It has been shown that reattachment without any additional preparation recovers only 50% of the fracture resistance as compared to a sound tooth. 24 Srilatha et al 25 have reported a fracture strength recovery of around 36.6% compared to a sound tooth in simple reattachment technique which suggests that this technique results in a fracture strength of even less than 50% of a sound tooth. On the contrary, Worthington et al 26 reported no difference in the bond strength in teeth reattached with simple technique compared to those with additional preparation.…”
Section: Techniques For Fragment Reattachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that, in comparison to a healthy tooth, reattachment restores 50% of fracture resistance [ 15 ]. Srilatha et al conducted a study on fragment reattachment and found that a simple fragment reattachment procedure recovers fracture strength by nearly 36.6% compared to a sound tooth [ 16 ]. Worthington et al, on the other hand, employed a straightforward reattachment method and discovered no variation in the bonding strength between teeth that were reattached without further preparation [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…According to Diangelis and Jungbluth, inhibition of eventual darkening because of dentine devitalization in the fragment and an increase in bond strength are provided by an internal dentine groove preparation [ 23 ]. In a study comparing four different reattachment techniques, Srilatha et al found that, in comparison to a sound tooth, the internal dentine groove can regain fracture strength by 89.2% [ 16 ]. According to Kulkarni et al, labial double chamfer with lingual overcontouring (54.49%), labial and lingual double chamfer (51.31%), and simple reattachment (28.27%) showed the maximum recovery of fracture resistance.…”
Section: Reviewmentioning
confidence: 99%